2012
DOI: 10.1093/geronb/gbs112
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Need for Cognition, Cognitive Activity, and Depressive Symptomatology With Cognitive Function in Recent Retirees

Abstract: Our findings indicate that motivational disposition plays a significant role in enhancing cognitive status in retirees, as do variety of cognitive activities. Additionally, subclinical depressive symptomatology can negatively influence cognitive status in young-old retirees. These results have implications for the design of interventions aimed at maintaining the cognitive health of retirees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 48 publications
2
31
1
2
Order By: Relevance
“…A possible explanation is that whereas immediate word recall reflects working memory capacity, delayed story recall is driven by more elaborate encoding and semantic processes (Park et al 2014). Thus, the DT training may have conferred greater benefits to individuals without ongoing cognitive stimulation (i.e., low NFC), but at the same time, a cognitively enriched lifestyle associated with high NFC (Baer et al 2012) might support long-term memory encoding and retrieval. Together, the moderation findings have methodological implications, in that cognitive training programs should consider the match between participant characteristics (e.g., baseline fitness, motivation to seek out intellectual stimulation) and the type of outcome measures.…”
Section: Moderators Of Training Gainsmentioning
confidence: 99%
“…A possible explanation is that whereas immediate word recall reflects working memory capacity, delayed story recall is driven by more elaborate encoding and semantic processes (Park et al 2014). Thus, the DT training may have conferred greater benefits to individuals without ongoing cognitive stimulation (i.e., low NFC), but at the same time, a cognitively enriched lifestyle associated with high NFC (Baer et al 2012) might support long-term memory encoding and retrieval. Together, the moderation findings have methodological implications, in that cognitive training programs should consider the match between participant characteristics (e.g., baseline fitness, motivation to seek out intellectual stimulation) and the type of outcome measures.…”
Section: Moderators Of Training Gainsmentioning
confidence: 99%
“…Other activities commonly associated with people with high Need for Cognition levels might include searching, acquiring, and reflecting about information, all of which correspond to activities that could potentially decrease the risk of subsequent cognitive deficits. Despite this potential association, to our knowledge, these studies evaluated the association between need for cognition and cognitive ability only within local samples that do not mirror representative of the entire United States population [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, higher levels of Need for Cognition have been found to lead toward increased cognitive ability in up to two years [6]. Other studies found that self-reported engagement in cognitive leisure activities was associated with a slow onset of memory impairment among dementia patients [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations